Policies for improved land management in Uganda: Second National Workshop - Nkonya, Ephraim M.; Sserunkuuma, Dick; Pender, John L. (International Food Policy Research Institute, 2002)
Contents: Welcome And Introduction; Opening of the Workshop; Policies for Improved Land Management in Uganda: Project Objectives, Activities, and Opportunities; Summary of Main Themes and Key Findings; Development Pathways and Land Management in Uganda: Causes and Implications; A Spatially Based Strategic Planning Framework for Sustainable Land Use in Uganda; Alternative Growth Scenarios for Ugandan Coffee to 2020; Potentials And Constraints to Coffee Development: Aiding the Coffee Replanting Program; The Relationship Between Socio-Economic Characterisitics of Maize Farmers and Household Food Security in Eastern Uganda; Land Management Problems and Potentials in the Lakeshore Intensive Banana-Coffee Farming System; A Review of Land Use Change and Soil Degradation in the Southwestern Highlands of Uganda; Ugandan Crop Market Development: Characteristics, Constraints and Opportunities; Dynamics of Maize Market Integration in Post-Liberalized Uganda; Information Asymmetry Among Output Traders, Processors and Farmers in Uganda; Determinants and Implications of Development Pathways and Land Management in Uganda; Soil Conservation Practices and Non-Agricultural Activites in the Southwestern Highlands of Uganda; Common Property and Collective Action in Natural Resource Management: The Case of Doho Rice Scheme in Tororo District, Eastern Uganda; Motivating Smallholder Investments in Sustainable Land Management: Emerging Roles For NGOs and CBOs in Uganda; Soil Organic Matter and Its Relationship to Soil Fertility Changes in Uganda; Determinants of Nutrient Balances In Maize Plots In Eastern Uganda; The Potential Benefit of Velvet Bean (Mucuna Pruriens) And N Fertilisers in Maize Production on Contrasting Soils in Uganda; Modelling Approach to Identify Sustainable Land Management Techniques on Erosion-Affected Slopes; Technologies for Improved Livelihood in Southwestern Uganda; Land Management and Technology Adoption in Uganda: An Integrated Bio-Economic Modeling Approach; Modeling Policy Impacts Using an Agriculture-Focused Cge Model; Appendix A: Workshop Agenda; Appendix B: List of Participants